Evaluasi Fungsi Ekologis Pohon Pada Alun-Alun Merdeka Malang - Caesa Adzania Zahra; Rosyi Damayanti Twinsari Manningtyas; Tati Budiarti (Jurnal Lanskap Indonesia, 2026)
City parks play an important role in improving the quality of the urban environment. Therefore, it is necessary to evaluate the ecological function of trees to find out how effective the trees in city park in providing ecological functions. The objective of this study was to identify landscape characteristics, then evaluate the ecological functions of trees including carbon absorption, carbon storage, and oxygen production. The research was conducted in Alun-Alun Merdeka, Malang, which has an area more than 5000 ?2 dominated by trees. Data collection is done by field measurement, observation, and literature reference. In this study, I-Tree Eco was used to analyze the data. The result shows that Alun-Alun Merdeka is capable of absorbing 1,388 tons of carbon/year, storing 202.9 tons of carbon, and producing 3,702 tons of oxygen/year. Species of trees that are able to absorb carbon as well as produce high oxygen in Alun-Alun Merdeka are Angsana (Pterocarpus indicus), Umbrella (Filicium decipiens), and Norfolk Cemara (Araucaria heterophylla), while species that are capable of storing carbon in large quantities are (Ficus benjamina), Bodhi (Ficus religiosa), and Glodogan (Polyalthia longifolia). At last, the effective species to enhance ecological function is recommended by providing tables and planting plan. This research provides scientific reference to tree species that are effective in providing ecological functions using I-Tree Eco in Alun-Alun Merdeka Malang.